South African Heart Association Newsletter - Authors, Various (SA Heart Journal, 2017)
<table style="border: 0px; border-spacing: 0px; font-size: 11.2px; color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #fbfbf3;" width="441"> South African Heart Association Newsletter - <span style="color: #111111; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 11.2px; font-style: italic; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #fbfbf3; display: inline !important; float: none;">Various Authors